Family involvement and hotel online reputation - J. Diéguez-Soto; M. A. Fernández-Gámez; Gregorio Sánchez Marín (BRQ Business Research Quarterly, 2017)
Online reputation is nowadays particularly significant in the context of hotel firms due to the high sensitivity and enormous influence of electronic word-of-mouth activities of customers. Since there is still no clear set of online reputation-generating factors, the aim of this paper is to contribute to this knowledge considering the role of family governance as an antecedent of hotel online reputation. Specifically, our purpose is to explain whether the heterogeneity among family firms regarding their family influence on the business exerts a significant effect on online reputation of hotel firms, investigating how family ownership and family management dimensions interact in terms of influencing online reputation. Our findings, based on a sample of 157 Spanish family hotels, indicate a positive influence of family ownership on a hotel's online reputation, augmented by a positive moderating effect of the family management represented by the presence of a family CEO managing the hotel."
Keywords: 650; Family involvement; Family ownership; Family CEO; Online reputation; Hotel industry